Vulnerability of firn to hydrofracture: poromechanics modeling - Yue Meng; Riley Culberg; Ching-Yao Lai (Journal of Glaciology)
On the Greenland Ice Sheet, hydrofracture connects the supraglacial and subglacial hydrologic systems, coupling surface runoff dynamics and ice velocity. In recent decades, the growth of low-permeability ice slabs in the wet snow zone has expanded Greenland's runoff zone, but observations suggest that surface-to-bed connections are rare, because meltwater drains through crevasses into the porous firn beneath ice slabs. However, there is little quantitative evidence confirming the absence of surface-to-bed fracture propagation. Here, we use poromechanics to investigate whether water-filled crevasses in ice slabs can propagate vertically through an underlying porous firn layer. Based on numerical simulations, we develop an analytical estimate of the water injection-induced effective stress in the firn given the water level in the crevasse, ice slab thickness, and firn properties. We find that the firn layer substantially reduces the system's vulnerability to hydrofracture because much of the hydrostatic stress is accommodated by a change in pore pressure, rather than being transmitted to the solid skeleton. This result suggests that surface-to-bed hydrofracture will not occur in ice slab regions until all pore space proximal to the initial flaw has been filled with solid ice.